Outcomes of covered expandable stents for the treatment of TASC D aorto-iliac occlusive lesions. (December 2015) - Tewksbury, Robert; Taumoepeau, Lupe; Cartmill, Andrew; Butcher, Anna; Cohen, Toby
Introduction: Aortoiliac arterial occlusive disease is frequently encountered in the management of lower limb vascular insufficiency. We report our experience with covered balloon-expandable stents for treatment of TASC D lesions of the abdominal aorta and common iliac arteries. Methods: A retrospective study of 30 patients who underwent aortoiliac stenting with the Atrium Advanta V12 from March 2010 to September 2012 was conducted. Patient demographic data, clinical signs and symptoms and procedural details were recorded. Outcomes assessed were primary patency, secondary patency, technical success, complications, limb salvage and survival. Results: Median age was 67 years (range 48–84) and 40% of patients underwent treatment for critical limb ischaemia. Median follow-up was 13 months (range 3–38 months). Stent configuration comprised of long iliac stents in 20 patients, a large diameter aortic stent with iliac stenting in six patients, and aortic stent alone in four patients. Radiological success was achieved in 100% and the complication rate was 6%. Primary patency at 6, 12 and 24 months was 97%, 90% and 79%, respectively. Four cases of in-stent stenosis were reported, with three of these undergoing re-interventions resulting in a secondary patency rate of 97% at the end of follow-up. One patient death occurred within the follow-up period. Discussion: This case series demonstrates that treatment of complex aortoiliac occlusive disease with covered balloon-expandable stents can have acceptable results with good patency and good clinical outcome. Secondary patency rates are comparable to open surgical revascularisation, with lower morbidity.